A Straightforward Approach towards Functionalized Amino Acids and Pipecolinic Acids via Ruthenium-Catalyzed Allylic Alkylation - Servatius, Phil; Kazmaier, Uli (Synlett, 2015)
Chelated amino acid ester enolates react with cis-butene diol substrates via Ru-catalyzed allylic alkylations to functionalized amino acids. The use of [(p-cymene)RuCl2]2 as catalyst allows the introduction of Z-configured allylic alcohols in the side chain of the amino acid. They facilitate access to pipecolinic acid and baikiaine derivatives.
Keywords: amino acids; allylic alkylation; ruthenium catalysis; cis-butene diol substrates; pipecolinic acid; baikiain